2017
DOI: 10.1177/1933719116667228
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs in Murine Experimental Endometriosis: Decreased Abundance of let-7a

Abstract: Endometriosis is a chronic disease that commonly affects women of reproductive age; however, diagnosis is often delayed due to lack of appreciation of early signs and symptoms. Development of a noninvasive biomarker would significantly reduce delays in diagnosis and treatment. Circulating microRNAs (miRNAs) have been implicated as biomarkers for several diseases including endometriosis. Here, we use an miRNA array to investigate differential miRNA abundance in the serum of mice after induction of experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Previous work in endometriosis has also corroborated our findings, with a report indicating that let-7a is downregulated in serum in a mouse model of endometriosis (28), miR-23a is upregulated in ectopic compared with eutopic tissues (29), and differential expression of miR-143 and -320a in endometriomas is shown compared with endometrium (24). Our qPCR-based validation studies involved additional DE miRNAs from Supplemental Table 1 of commonly grouped DE miRNAs such as miR-29c, which has been reported to be downregulated in ectopic endometrium (30), as well as miR-451, which is elevated in endometriotic tissue compared with paired eutopic endometrium from women with disease in the patient cohort from (29) (Ectopic > Normal and Eutopic > Normal tissues as detected in the small RNA-seq data).…”
Section: Discussionsupporting
confidence: 91%
“…Previous work in endometriosis has also corroborated our findings, with a report indicating that let-7a is downregulated in serum in a mouse model of endometriosis (28), miR-23a is upregulated in ectopic compared with eutopic tissues (29), and differential expression of miR-143 and -320a in endometriomas is shown compared with endometrium (24). Our qPCR-based validation studies involved additional DE miRNAs from Supplemental Table 1 of commonly grouped DE miRNAs such as miR-29c, which has been reported to be downregulated in ectopic endometrium (30), as well as miR-451, which is elevated in endometriotic tissue compared with paired eutopic endometrium from women with disease in the patient cohort from (29) (Ectopic > Normal and Eutopic > Normal tissues as detected in the small RNA-seq data).…”
Section: Discussionsupporting
confidence: 91%
“…75 In 2008, miRNA analysis by Ohlsson Teague et al demonstrated that 22 miRNAs were differentially expressed in human endometriosis lesions compared with eutopic endometrium. 76 Since then, miRNAs in endometriosis have been investigated as endometriosis biomarkers analysis 8,77,78 and for insight into disease proliferation and pathogenesis. 76,[79][80][81][82][83][84][85] In addition to affecting the endometriosis lesion microenvironment, miRNAs are secreted into the vasculature near the lesion and alter systemic serum miRNA concentrations.…”
Section: The Role Of Micro-rnas In Endometriosismentioning
confidence: 99%
“…76,[79][80][81][82][83][84][85] In addition to affecting the endometriosis lesion microenvironment, miRNAs are secreted into the vasculature near the lesion and alter systemic serum miRNA concentrations. 8,77,78 In 2016, miRNA microarray and qPCR analysis of patient serum samples demonstrated that 10 microRNAs were more than 10-fold aberrantly regulated, Mir-125b-5p, miR-150-5p, miR342-3p, miR-145-5p, miR-143-3p, miR-500a-3p, miR-451a, miR18a-5p, miR-3613-5p, and miR-6755-3p. 8 Several of these circulating miRNAs have been correlated with chemoresistant breast cancer, breast cancer development, and suppression of the differentiation of mesenchymal stem cells, a possible source of endometriosis lesions.…”
Section: The Role Of Micro-rnas In Endometriosismentioning
confidence: 99%
“…Distinct miRNA expression profiles have been identified in microarray studies of eutopic and ectopic endometrial tissue samples . We previously reported that circulating microRNAs, including Let‐7b‐5p, were significantly decreased in the serum of patients with endometriosis as well as animal models of the disease . Further, we have reported decreased Let‐7 family members in endometriosis tissue where they are involved in the regulation of genes such as KRAS and aromatase .…”
Section: Introductionmentioning
confidence: 98%